1987
DOI: 10.1182/blood.v70.2.516.516
|View full text |Cite
|
Sign up to set email alerts
|

Effects of herpes virus carrier status on peripheral T lymphocyte subsets

Abstract: We studied the effects of herpes virus carrier status on peripheral blood T lymphocyte subsets in 334 healthy individuals. IgG-class antibodies against cytomegalovirus (CMV), Epstein-Barr virus (EBV), herpes simplex virus (HSV), and varicella-zoster virus (VZV) were used as markers for the carrier status of those viruses. CMV carrier status was associated with significant increases in the numbers of some T cell subsets, whereas the carrier status of EBV, HSV, and VZV had no significant effects. The 159 CMV-ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…Table 2 shows the results of the comparisons between (i) PNS versus SCLC; (ii) PNS versus HC; and (iii) SCLC versus HC, after adjusting for the influences of age, gender and CMV serostatus. In agreement with earlier observations [33][34][35][36], increasing age was associated with significantly lower numbers of B cells,…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Table 2 shows the results of the comparisons between (i) PNS versus SCLC; (ii) PNS versus HC; and (iii) SCLC versus HC, after adjusting for the influences of age, gender and CMV serostatus. In agreement with earlier observations [33][34][35][36], increasing age was associated with significantly lower numbers of B cells,…”
Section: Discussionsupporting
confidence: 93%
“…Age, gender and CMV serostatus have significant impacts on the numbers and phenotypes of the lymphocyte subsets under study [33][34][35][36]. Therefore, paired comparisons between the various groups were performed using ANCOVA with covariates CMV serostatus, age and gender [SPSS version 11.5 (SPSS Inc., Chicago, IL, USA)].…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with chronic CMV infection have a more differentiated peripheral blood CD8 T-cell population than uninfected individuals. [2][3][4][5][6]13 We found an increase in the proportion of differentiated CD8 T cells was caused by an increase in the absolute number of differentiated cells, defined by loss of CCR7, CD28 and CD27, and expression of CD57. Also, the number of undifferentiated CD8 T cells was unaffected by CMV infection.…”
Section: Discussionmentioning
confidence: 71%
“…1 Chronic infection of senior citizens is associated with a large expansion of the differentiated CD28 ) CD57 + subpopulation of CD8 T-cells and a smaller expansion of the equivalent subpopulation of CD4 T-cells. [2][3][4][5][6][7] The expansion of differentiated, and possibly immunosenescent, CD8 T-cells contributes to an 'immune risk phenotype', 8 which may also include an inversion of the ratio of CD4 and CD8 T-cells in extreme cases. 3,5 Both the immune risk phenotype 9,10 and CMV infection 11 are associated with poor responses to the influenza vaccine and to Epstein-Barr virus (EBV), 12 another persistent herpesvirus.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies on the composition of the different T cell subsets indicated that CMV infection markedly altered their ratios 6 and reported expansions of CD8 + CD57 + subsets in CMV-seropositive individuals. Increases of cells with this same phenotype were independently found to be associated with increasing age in other studies.…”
Section: Hypothesismentioning
confidence: 99%